PARP1 Represses PAP and Inhibits Polyadenylation during Heat Shock - Di Giammartino, Dafne Campigli; Shi, Yongsheng; Manley, James L. (Molecular cell, 2013)
The 3′ ends of most eukaryotic mRNAs are produced by an endonucleolytic cleavage followed by synthesis of a poly(A) tail. Poly(A) polymerase (PAP), the enzyme that catalyzes the formation of the tail, is subject to tight regulation involving several posttranslational modifications. Here we show that the enzyme poly(ADP-ribose) polymerase 1 (PARP1) modifies PAP and regulates its activity both in vitro and in vivo. PARP1 binds to and modifies PAP by poly(ADP-ribosyl)ation (PARylation) in vitro, which inhibits PAP activity. In vivo we show that PAP is PARylated during heat shock, leading to inhibition of polyadenylation in a PARP1-dependent manner. The observed inhibition reflects reduced RNA binding affinity of PARylated PAP in vitro and decreased PAP association with non-heat shock protein-encoding genes in vivo. Our results provide direct evidence that PARylation can control processing of mRNA precursors, and also identify PARP1 as a regulator of polyadenylation during thermal stress. [Display omitted] ► PARP1 binds and PARylates PAP in vitro, which inhibits its polyadenylation activity ► Polyadenylation is inhibited during heat shock in a PARP1-dependent manner ► PAP is PARylated in vivo during heat shock ► Inhibition of polyadenylation reflects decreased RNA binding by PARylated PAP